Topik-Topik dalam Buku Ajar BIPA Let’s Speak Indonesian: Ayo Berbahasa Indonesia 1 - Hanifia; Gatut Susanto; Ariva Luciandika (Universitas Negeri Malang, 2021)
Abstract: The Language Development and Cultivation Agency (2012) explains that BIPA is an Indonesian language learning process targeted to foreigners who are interested in learning Indonesian for a specific purpose. The process of learning Indonesian in general cannot be equated with learning Indonesian for foreign speakers. The textbook used contains materials used for teachers in implementing the learning process. The materials cover knowledge, skills that students must learn to achieve goals by competency standards. Because that's the use of language that suits the students' abilities. The purpose of this research is to describe the topics in the teaching material